No-tillage does not on average reduce soil carbon storage compared to conventional tillage. Comment on “Declines in soil carbon storage under no tillage can be alleviated in the long run” by Cai et al. - Simpson, Zachary P. (2023)
Cai et al. (2022) presented a meta-analysis of how no-tillage (NT) practices, in comparison to a conventional tillage (CT) practice, affect soil organic carbon (SOC) stocks. They concluded that NT, relative to CT, increased SOC only in the upper soil depth (0–10 cm) but reduced SOC in some deeper layers, leading to an overall net decrease of SOC across the profile (up to 60 cm deep; average of −0.24 Mg C ha−1). As researchers interested in how agricultural conservation practices, such as NT or reduced tillage, can improve ecosystem services like soil carbon storage, we were surprised by these results: several past meta-analyses on the same topic arrived at opposite conclusions (e.g., Meurer et al., 2018, Nicoloso and Rice, 2021, West and Post, 2002). After re-analysis of the data presented by Cai et al. (2022), we found that the data do not support the authors’ conclusions but rather show support for NT as preferable to CT as a SOC storage practice.